The Role of Brand Personality in Moderating the Positive Emotions on Impulse Buying Tendency for Sparta Shoe Brand - Rafa, Gabriela Ditta Aurelya (Universitas Ciputra Surabaya, 2025)
This study investigates the influence of positive emotions on impulse buying tendencies, with brand personality serving as a moderating variable. Grounded in the Stimulus-Organism-Response (S-O-R) theory, the research explores how media stimuli specifically Instagram content reflecting brand personality affect consumers' impulsive purchasing behavior. A quantitative approach was employed, involving 260 respondents aged 18–39 who are users of local shoe products and followers of the Instagram account @spartashoes.id. Data were analyzed using Structural Equation Modeling (SEM) with IBM SPSS AMOS. The findings reveal that positive emotions significantly drive impulse buying tendencies. Moreover, brand personality enhances these emotional responses, further increasing the likelihood of impulsive purchases. Key brand personality dimensions that emerged as influential include competence, sophistication, and ruggedness. These traits effectively stimulate emotional engagement and spontaneous consumer decisions. The study highlights the strategic importance for local brands to cultivate a strong brand personality in digital media to better capture consumer interest and competitiveness in Indonesia’s local market landscape